Spatial Self-Organization as a New Perspective on Cold-Water Coral Mound Development - van der Kaaden, Anna-Selma; van Oevelen, Dick; Rietkerk, Max; Soetaert, Karline; van de Koppel, Johan (Frontiers in Marine Science, 2020)
Cold-water corals build extensive reefs on the seafloor that are oases of biodiversity, biomass, and organic matter processing rates. The reefs baffle sediments, and when coral growth and sedimentation outweigh ambient sedimentation, carbonate mounds of tens to hundreds of meters high and several kilometres wide can form. Because coral mounds form over ten-thousands of years, their development process remains elusive. While several environmental factors influence mound development, the mounds also have a major impact on their environment. This feedback between environment and mounds, and how this drives mound development is the focus of this paper. Based on the similarity of spatial coral mound patterns and patterns in self-organized ecosystems, we provide a new perspective on coral mound development. In accordance with the theory of self-organization through scale-dependent feedbacks, we first elicit the processes that are known to affect mound development, and might cause scale-dependent feedbacks. Then we demonstrate this concept with model output from a study on the Logachev area, SW Rockall Trough margin. Spatial patterns in mound provinces are the result of a complex set of interacting processes. Spatial self-organisation provides a framework in which to place and compare these processes, so as to assess if and how they contribute to pattern formation in coral mounds.